Proactive Approach to the Deployment of 5G Technology: Insights from the UAE - Sultan Ahmed AlRaeesi AlBalooshi; Mohammad Habibur Rahman (International Telecommunications Society (ITS), 2019)
The task of introducing innovative 5G technology is an urgent one for digital development. This study perceives 5G technology from evolving global perspectives and provides a particular focus on its policy landscape in the UAE that includes state and other stakeholders. The paper starts with a literature review that underpins the various notions on this new wireless network, describes the stakeholders involved and highlights the preparations for launch. Based on a quick qualitative survey through interviews of three key personalities from three principal stakeholders (i.e. the Telecommunications Regulatory Authority [TRA] as the regulator, Etisalat as the service provider and Ericsson as the vendor) the paper assesses the views of the key stakeholders on the new 5G technology and their opinions concerning the nuances of its introduction. The analysis of the data presented demonstrates the high expectations placed on the 5G network and its capacity which is associated with some challenges that needs to be overcome primarily through collaboration and proactive approach. The purpose of this study is to determine which factors are considered by the state as ways of modernising the existing digital base in the UAE.
Keywords: 330; 5G; network; initiative; technology; digital; introduction; TRA